2010
DOI: 10.1155/2010/942874
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Cytomegalovirus Infection in High‐Risk Canadian Infants: Report of a Pilot Screening Study

Abstract: A cCMV screening program should be universal and routine to successfully screen all newborns. Maternal CMV seropositivity varies widely within the Canadian population. In the present pilot study, DBS PCR was not a sensitive screening tool and throat swab was the best screening specimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 49 publications
1
24
1
2
Order By: Relevance
“…Duration of previous hospitalizations did not prove to be a risk factor in this study in spite of the literary data. 9 Prematurity is a risk factor according to some authors 9,15 , but this fi nding is refuted by others 5,10,11 , as do the authors of the present study. Low family income, rearing in an orphanage and infusion of bioproducts, which showed no correlation with CMV infection in the present study, are risk factors according to some authors 1,9 but not to others 11,15 .…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Duration of previous hospitalizations did not prove to be a risk factor in this study in spite of the literary data. 9 Prematurity is a risk factor according to some authors 9,15 , but this fi nding is refuted by others 5,10,11 , as do the authors of the present study. Low family income, rearing in an orphanage and infusion of bioproducts, which showed no correlation with CMV infection in the present study, are risk factors according to some authors 1,9 but not to others 11,15 .…”
Section: Discussioncontrasting
confidence: 52%
“…[1][2][3] The population rate of congenital CMV infection ranges from 0.04% to 2.2% depending on geographical and socio-economic factors. 2,4,5 Studies conducted in Bulgaria between 1992 and 1997 showed the congenital CMV infection to have a relatively high incidence rate (2.4%) in newborns. 6 However, most of the infections occurring in the fi rst year of life are postnatal or perinatal as a result of which more than one-third of children are CMV seropositive at about 12 months of age.…”
Section: Introductionmentioning
confidence: 99%
“…The suboptimal sensitivity of the DBS PCR approach was also observed in the present study, in which only half of the newborns with confirmed congenital CMV infection had positive PCR in their DBS samples (Table I). The main factors influencing the low sensitivity of the DBS PCR approach are a lower viral load present in the blood (also observed in this study), the size of DBS used for PCR testing, the choice of method used for DNA extraction and the PCR assay's analytical characteristics [Vaudry et al, 2010;Leruez-Ville et al, 2011]. Body fluids with a higher viral load, such as urine are presumably less affected when using one of the listed less efficient variables.…”
Section: Discussionmentioning
confidence: 54%
“…Molecular methods, such as PCR, are considered currently to be the most appropriate methods for CMV screening of newborns but the question of which clinical sample is best suited for large-scale neonatal CMV screening is still unresolved [Boppana et al, 2010[Boppana et al, , 2011Vaudry et al, 2010;Cannon et al, 2011]. Although three clinical samples, urine, plasma, and DBS, were collected from each neonate for the present study, only urine was screened for CMV DNA due to financial constraints.…”
Section: Discussionmentioning
confidence: 99%
“…In Canada, the reported prevalence rate is 0.4 to 1.7% (2). The fetus is infected by viral transmission via the placenta following an episode of viremia in the mother (1).…”
mentioning
confidence: 99%